Towards a re‐conceptualization of flow in social contexts - Hackert, Benedikt; Lumma, Anna‐Lena; Raettig, Tim; Berger, Bettina; Weger, Ulrich (Journal for the theory of social behaviour, 2023)
The antecedents and outcomes of individual‐level flow are well documented in a large body of literature. However, flow does not only occur in isolation ‐ quite to the contrary, recent evidence suggests that social interaction can facilitate the experience of flow. Therefore, we propose a taxonomy, which distinguishes five different flow states according to two global factors: interactional synchrony and self‐other overlap. Solitary flow bears all characteristics developed by Csikszentmihalyi. Co‐active flow is facilitated or hampered by the presence of other people. Private interactive flow emerges on the grounds of a minimal unidirectional interaction with more passive others; only the active subject is in flow. In shared interactive flow, a fully synchronized activity between group members takes place and all group members are in flow. In group flow, all members reach a level of complete self‐other overlap with the group, which leads to a collective experience of flow on the group‐level. In addition to differences and commonalities of the different types of flow, suggestions for how to induce and study social flow are discussed.